(untitled) (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2018)
Infancy is the period a very important life and need special attention from the parents. Most parents are instrumental in growing flower child is the mother. Attitude isÂ thought to be theÂ function of theÂ knowledge gainedÂ through the mediaÂ ad impressions. This research the correlation of knowledge and the ads exposure food and knowledge about advertising with the attitude of the mother in the giving of food on a toddler. Type of this research in quantitative research with survey method of qualitative data supported by in-depth in interview method. Respondents consist of 40 of mother. The results showed a significant correlation ads exposured levels against the level of knowledge of the mother and the level of knowledge of the food the mother has in giving food on toddlers. Keywords: ads exposured, attitude, knowledge ——————-Â ABSTRAK Masa balita merupakan masa kehidupan yang sangat penting dan perlu perhatian yang khusus dari orangtua. Orangtua yang paling berperan dalam tumbuh kembang anak adalah ibu. Sikap diduga merupakan fungsi dari pengetahuan yang diperoleh melalui media tayangan iklan. Penelitian ini bertujuan untuk mengetahui hubungan keterdedahan iklan tentang pangan dan pengetahuan dengan sikap ibu dalam memberi pangan pada balita. Jenis penelitian ini adalah penelitian kuantitatif dengan metode survei yang didukung data kualitatif dengan metode wawancara mendalam. Responden terdiri dari 40 orang ibu. Hasil penelitian menunjukkan tingkat keterdedahan memiliki hubungan signifikan dengan tingkat pengetahuan ibu dan tingkat pengetahuan pangan ibu tidak memiliki hubungan signifikan dengan sikap ibu dalam memberi pangan pada balita.Â Kata kunci: keterdedahanÂ iklan, pengetahuan, sikap